A Sample of Extreme Eclipsing Binaries with Accretion Disks from LAMOST and ZTF - Jiangxinxin Zhuang; Zhi-Xiang Zhang; Wei-Min Gu; Senyu Qi (The Astrophysical Journal)
Extreme eclipsing binaries may harbor peculiar physical properties. In this work, we aim to identify a sample of such systems by selecting binaries with pronounced eclipsing light curves, characterized by large variability (Δmag > 0.3 in the g band of the Zwicky Transient Facility, ZTF) and significant differences between primary and secondary eclipses (eclipse depth ratio >20 in the ZTF g band). We identified 23 candidates by combining the photometric data and the LAMOST spectroscopic survey. Spectroscopic analysis revealed that all of these systems are dominated by A-type stars in the optical band. Further investigation confirmed that all 23 candidates are Algol-type binaries, with 22 of them being newly discovered. Their orbital periods range from 2.57 to 19.21 days. These systems consist of low-luminosity, highly stripped subgiant donors and accreting A-type stars. The donor stars, with radii of 2.5–8.9 R _⊙ and effective temperatures around 4000 K, have typical masses of M _2  ∼ 0.3 M _⊙ , indicating substantial mass loss through Roche-lobe overflow. The presence of ellipsoidal variability and H α emission provides strong evidence for ongoing mass transfer. By fitting the spectral energy distributions, spectra, and light curves, we found that most of the accretors have luminosities lower than expected from the mass–luminosity relation, aligning with the predicted faint phase for mass-gaining stars. Three objects of our sample exhibit pulsations with periods from 18 minutes to 8 hr, providing opportunities for asteroseismic studies. The low mass transfer rates and stability make the sample excellent systems for studying mass accretion, advancing our understanding of the evolution of Algol-type binaries.